Banking crisis: Empirical evidence of Iranian bankers - Mahdi Salehi; Ali Mansouri; Reza Pirayesh (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
It is generally understood that well functioning banks and financial institutions help promote economic growth. That's why Iranian government is trying to play active role to promote economic growth through well established banking and financial system. This survey shows that after interference of Iranian government in banking sector the going concern of Iranian banks became sustainable. However, the interference raises higher level of inflation in Iranian economy.
Keywords: 330; Bank crisis; Survival; Inflation; and Iran